The Effect of Fast Kr Ion Irradiation on the Optical Absorption, Luminescence, and Raman Spectra of BaFBr Crystals; Crystals; Vol. 13, iss. 6 - Akylbekov A. T. Abdrash Tasanovich; Kenbaev D. Daurzhan; Dauletbekova A. K. Alma Kezhemkulovna; Polisadova E. F. Elena Fyodorovna; Yakovlev V. Yu. Viktor Yurjevich; Karipbaev Zh. Zhakyp; Shalaev A. A. Aleksey Aleksandrovich; Elsts E. Edgars; Popov A. I. Anatoly Ivanovich (2023, 2023)
Title screen